2019
DOI: 10.1002/ente.201900617
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimal Metal–Organic Frameworks for Adsorption Chillers: Insights from the Scale‐Up of MIL‐101(Cr) and NH2‐MIL‐125

Abstract: The metal-organic frameworks (MOFs) MIL-101(Cr) and NH 2-MIL-125 offer high adsorption capacities and have therefore been suggested for sustainable energy conversion in adsorption chillers. Herein, these MOFs are benchmarked to commercial Siogel. The evaluation method combines small-scale experiments with dynamic modeling of full-scale adsorption chillers. For the common temperature set 10/30/80 C, it is found that MIL-101(Cr) has the highest adsorption capacity, but considerably lower efficiency (À19%) and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…A comparison of such a packed bed performance of MIL-101(Cr) and NH 2 -MIL-53(Al) shows that mass and heat transport are slow in these systems, resulting in lower efficiency and power density than a silica gel. 336 Betke et al improved the heat transportation of CAU-10 (0.08 W m –1 K –1 for compacted pellet) by intergrowth with reticulated open-cellular alumina foams (0.9–1.78 W m –1 K –1 ). 349 Heat exchangers coated with the adsorbent are by far superior to packed beds, similar as for catalytic reactors, 28 in terms of power delivered per mass of adsorbent.…”
Section: Applications and Performance Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of such a packed bed performance of MIL-101(Cr) and NH 2 -MIL-53(Al) shows that mass and heat transport are slow in these systems, resulting in lower efficiency and power density than a silica gel. 336 Betke et al improved the heat transportation of CAU-10 (0.08 W m –1 K –1 for compacted pellet) by intergrowth with reticulated open-cellular alumina foams (0.9–1.78 W m –1 K –1 ). 349 Heat exchangers coated with the adsorbent are by far superior to packed beds, similar as for catalytic reactors, 28 in terms of power delivered per mass of adsorbent.…”
Section: Applications and Performance Assessmentmentioning
confidence: 99%
“… 396 , 397 The use of binders and coatings is used to alleviate this drawback. 280 , 336 Because not only conduction plays a role but also the heat capacity of the materials, a better parameter to characterize the thermal transport is the thermal diffusivity a = λ/(ρ· c p ) [m 2 s –1 ] that describes how fast temperature profiles move in the system (see Figure 2 ). The low heat capacity is positive in this sense, but particle and bed porosity and conductive support structures have an adverse effect.…”
Section: Evaluation and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…kW m –3 ) MOFs are only partly competitive to commercial silica gels due to the low specific density of MOFs. [ 140 ] Therefore, MOFs have to become more competitive in terms of cost per (volume) specific power. This may either be achieved by adjusting material characteristics in terms of higher uptake per volume of MOF or by improving heat and mass transfer by optimized shaping technologies.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…For instance, some MOFs, such as MIL-100 and MIL-101 families, have recently attracted high attention due to their high capacity of water adsorption (Canivet et al, 2014). Graf et al (2020) have carried out experimental investigations on the dynamics of water adsorption in two different MOFs; namely, MIL-101(Cr) and NH2-MIL-125, and compared them with Siogel, which is characterized by a relatively lower capacity for water adsorption. The study showed that, for the common temperature set 10/30/80 °C, MIL-101(Cr) has demonstrated the highest adsorption capacity, but with significantly lower COP (−19%) and volumetric cooling power (−66%) than Siogel.…”
Section: Introductionmentioning
confidence: 99%